Aplikasi Android Contruct 2 untuk Media E-Learning pada Materi Peluang - Ridho, Fachri; Anggoro, Bambang Sri; Andriani, Siska (Universitas Islam Negeri Raden Intan Lampung, 2019)
This study aims to produce an Android-based E-Learning learning media on opportunity material. This research method is Research and Development (R & D) based on Sugiyono's development model. The material expert's assessment of the learning media is included in the